DISCRIMINANT ANALYSIS OF SELECTED VARIABLES IN THE ADOPTION OF FISH CURING - BALASUBRAMANIAM, S; KAUL, P N (Fishery Technology, 2017)
Discriminant functions were worked out for adoption or non-adoption of five improved practices in fish curing. Four variables measured quantitatively formed the basis for discrimination. In four out of five equations, the selected variables were found to discriminate significantly between the adopters and non-adopters.